2001
DOI: 10.1177/153331750101600611
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Alzheimer's caregivers: Identifying risk factors

Abstract: Three risk factors were found to have a strong association with Alzheimer's caregiver depression. Early recognition of such risk factors may help to identify Alzheimer's caregivers with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
2
22
2
3
Order By: Relevance
“…This finding was initially surprising, and contrasts with previous studies, in which depression levels among caregivers have increased with lower autonomy in the dependent person (Covinsky et al, 2003;Molyneux et al, 2008). However, a previous study (Shua-Haim, Haim, Shi, Kuo, & Smith, 2001) also found that higher levels of functioning in dependent adults with Alzheimer's disease were related to higher depression in their caregivers. Given the age of dependent people in our samples, rates of dementia could be quite high, raising the hypothesis that behavioural disturbances common in the middle stages of Alzheimer's disease, when the dependent person still has some level of autonomy, account for the association between caregiver depression and higher autonomy in the dependent person; consistent with this hypothesis, the middle stages of Alzheimer's disease have been found to be a risk factor for caregiver depression in previous research (Zanetti et al, 1998).…”
Section: Discussioncontrasting
confidence: 52%
“…This finding was initially surprising, and contrasts with previous studies, in which depression levels among caregivers have increased with lower autonomy in the dependent person (Covinsky et al, 2003;Molyneux et al, 2008). However, a previous study (Shua-Haim, Haim, Shi, Kuo, & Smith, 2001) also found that higher levels of functioning in dependent adults with Alzheimer's disease were related to higher depression in their caregivers. Given the age of dependent people in our samples, rates of dementia could be quite high, raising the hypothesis that behavioural disturbances common in the middle stages of Alzheimer's disease, when the dependent person still has some level of autonomy, account for the association between caregiver depression and higher autonomy in the dependent person; consistent with this hypothesis, the middle stages of Alzheimer's disease have been found to be a risk factor for caregiver depression in previous research (Zanetti et al, 1998).…”
Section: Discussioncontrasting
confidence: 52%
“…13 Behavioral disturbances, such hallucinations and delusions of theft, have a strong association with poor caregiver outcomes in patients with dementia. [14][15][16] Hospitalization of dementia patients and deterioration of the patient-caregiver relationship have also been shown to increase caregiver burden. [17][18][19] Delirium often occurs in a hospital setting and is commonly characterized by hallucinations or paranoid delusions.…”
Section: Introduction Dmentioning
confidence: 99%
“…Patienten und Methodik: 42 Patienten mit diagnostizierter Demenz und ihre betreuenden Angehörigen nahmen an der prospektiven, randomisierten Studie und der Nachuntersuchung nach 18 Monaten teil. 29 Patienten erhielten zeitnah der Diagnosestellung eine psychosoziale Beratung. Neben Informationsvermittlung über die Erkrankung wurde über lokale Hilfsangebote informiert, der aktuelle Hilfebedarf ermittelt und ggf.…”
Section: Zusammenfassung ▼unclassified
“…Viele betreuende oder pflegende Angehörige von Patienten mit Demenzerkrankungen sind sehr belastet, 12 % bis 65 % erkranken an einer Depression [3,4,5,8,9,11,13,16,22,24,25,27,29,30,32,33]. Auch wenn objektive und subjektive Belastung durch die Betreuung Demenzkranker nicht in jedem Fall im Zusammenhang mit der Entwicklung einer klinisch fassbaren Depression stehen, so sind sie dennoch Prädiktoren für die Entwicklung einer Depression [7].…”
Section: Diskussion ▼unclassified